Coerced Literacies: A Critical Discourse Analysis of Volunteered Skills Training in Prison. (November 2018) - Litchfield, Kathrina
Without standardized access to higher education, incarcerated learners take advantage of the opportunities provided by local and national volunteer organizations for their postsecondary education. Toastmasters International describes itself as an educational nonprofit organization that teaches public speaking and leadership skills, which now expands its clubs into state and federal prisons. A Midwest region's district distributes a pamphlet that encourages Toastmaster members to volunteer time and money to support these prison clubs. Critical discourse analysis techniques are used to explore how language in this volunteer pamphlet appropriates social control, refigures prisoner identity, and positions learners through a deficit model of cognitive behavioral correctives. While this article examines only a single public text, my findings caution volunteer organizations to thoughtfully consider the assumptions and constructs they import when they enter the prison with intentions to rehabilitate or educate its residents.